ACCEPTABLE AUDIT RISK EVIDENCE IN JAKARTA INDONESIA - Mira Rahmi; Susi Indriani (Ekonomi dan Bisnis, 2017)
Early 20’s century begins with revealed some accounting financial scandals from reputable companies around the world’s where the economic crisis starts. Facts from some cases proofed that the auditors have weakness in assessing audit risk from those reputable companies (some are Enron (2001), worldcom (2002), Madoff (2008), and Saytam (2009)), recent years the scandals were happens to Japan companies where it hits Olympus (2011) and Toshiba (2015). Indonesia had Kimia Farma (2002) for example where the auditor were convicted less professional from assessing acceptable audit risk. The phenomena showed that auditors have big uncertainty of risk when they do the audit process and highly related to their integrity in doing the process. Assessment audit about clients will be influenced by the approach that was undertaken, audit planning program, risk assessment and how to analyze audit evidence (Bell et al; 2005). This research were aimed to give an empirical evidence on public accountants behavior in Jakarta, Indonesia when assessing acceptable audit risk based on their independent auditors. Using 11 public accountant offices in south and east Jakarta were picked randomly from OJK Public accountant offices Listed in 2015 with multivariate regression model between audit complexity, audit sampling judgment and management integrity toward acceptable audit risk. The result showed that the small portion of audit sampling judgment were set by the public accountants when they give their opiniondo makes the acceptable risk getting higher. Audit complexity and management integrity didn’t show related toward acceptable audit riskin public accountant offices in Jakarta during 2015.